Language translation from english to Malay in solid waste engineering - Rodzidah Mohd Rodzi; Noor Ezlin Ahmad Basri; Zulkifli Mohd Nopiah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Engineering translations are dense with technical jargon and terms that necessitate linguistic and field expertise. The challenges arise from the requirement that the target texts be idiomatic and retain the same phrasing order, meaning, and nuances as the source text, which a layperson cannot translate directly. The Malay language is Malaysia’s official language. Because Malay is the official language in the governing and executive constitutions, the research instrument should be available in Malay. The purpose of this research is to translate from English to Malay a qualitative risk framework for solid waste engineering. On three psychometric scales, 26 items were translated using a back-translation method involving eight linguistic experts. The Malaysian Institute of Translation and Books (ITBM) provided the primary translation, which was then reviewed by a panel of experts as a secondary translation. Next, content validation on a 5-point Likert scale was conducted with five civil engineering field experts to assess instrument structure and reliability agreement. To represent the expert validation process, a descriptive analysis of mean score agreement was performed. The studies discovered deviation losses in forward (8.98%) and backward (17.95%) translation. The results also revealed experts produce accurate translations, particularly the equivalents of engineering expressions, acronyms, measurements, and terminology. Eventually, expert consensus on six aspects was achieved for 27.8/30 (92.7%) and affirmed that the framework is valid and thus applicable. This paper recommends that translation requires quality control, which comprises three processes: conversion to the target language, comparison, and reconciliation by subject matter experts.